If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4n + 7 + 2n = 1 Reorder the terms: 7 + -4n + 2n = 1 Combine like terms: -4n + 2n = -2n 7 + -2n = 1 Solving 7 + -2n = 1 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2n = 1 + -7 Combine like terms: 7 + -7 = 0 0 + -2n = 1 + -7 -2n = 1 + -7 Combine like terms: 1 + -7 = -6 -2n = -6 Divide each side by '-2'. n = 3 Simplifying n = 3
| 4(x-2)=2(x+4) | | 5m=2m+12 | | 9y=50-y | | -3(4x-8)=-2(x+3) | | 11y+5=-15+6y | | 6n+8=38 | | 16h=8(2h-10) | | 58x+-10x=48x | | 12r=48+4r | | 4b-100=-b | | 3(5+x)=21 | | 3(5+x)=29 | | 6x-7w+5x+6y+4y+5w= | | 6x-19=4x+11 | | 3(x+4)-5(x-1)=9x-5 | | 26+7x=13x+7 | | 7x+3x(2+x)=12x | | 15a+19b+6c+5c-6b-3a= | | 18+6g=-12g | | 7x-11=39-3x | | 2d+9e+8d+11e= | | 15c-9c= | | -35=7(z-8) | | 4g-g= | | -2(a+16)=2 | | 8m+7+m=16 | | 92=9y-16 | | 12(2x-9)=3(8x+7) | | 2(x+5)(x+5)-22=0 | | -38-5x=7-10x | | 4x+3=2x-3 | | 59-5x=9x+17 |